Comparing the expression of human DNA topoisomerase I in KM71H and X33 strains of Pichia pastoris - Ruo, Ping Ang; Leong, Sin Teoh; Mooi, Kwai Chana; Miswan, Noorizan; Boon, Yin Khoo (Elsevier, 2016)
Human is an essential cellular enzymethat is found in all human cells. As this enzyme is upregulated in cancer cells exceedingly, it is used as a target for cancer chemotherapeutic drug development. As such, producing the in-house enzyme for the purpose to speed up the search for more cost-effective and target specific hTopoI inhibitors is warranted. This study aims to compare the optimised conditions for the expression of hTopoI in KM71H (MutS) and X33 (Mut+) strains of Pichia pastoris. P. pastoris transfected with an hTopoI recombinant vector was used for the optimization of a higher level of hTopoI expression. Results: In the process, fed-batch cultivation parameters that influence the expression of hTopoI, such as culture temperature, methanol induction and feeding strategy, were optimised in the transfected KM71H and X33 P. pastoris strains in a shake flask system. The cell density and total protein concentration (protein level) of transfected P. pastoris were compared to determine the optimum culture conditions for each transfected P. pastoris strain. A higher hTopoI level was observed in the transfected KM71H culture supernatant (2.26 ng/mL) when the culture was incubated in the optimum conditions. Conclusions: This study demonstrated thatMutS strain (KM71H) expressed and secreted a higher level of hTopoI heterologous protein in the presence of methanol compared to the Mut+ strain; X33 (0.75 ng/mL). However, other aspects of optimization, such as pH, should also be considered in the future, to obtain the optimum expression level of hTopoI in P. pastoris.